Kampanye Digital, Politik Lokal, dan Media Sosial - Fajar Mu'ti Abdillah; Abraham Zakky Zulhazmi (Faculty of Ushuluddin and Dakwah, UIN K.H. Abdurrahman Wahid Pekalongan, Central Java, Indonesia, 2021)
Today's digital-based branding self-image activities are common among political actors, Currently, political actors are starting to use social media as a medium for building self image. Instagram is one of the social media that is quite effective to use in self-image activities for politicians. One of the politicians who use Instagram as a digital campaign media to image themselves to the public is Kusdinar Untung Yuni Sukowati in his personal account, namely @mbakyuniselaludihati.This research uses semiotic analysis method. The researcher chose Charles Sanders Peirce's semiotic analysis method as the method of analysis. This researcher found that Kusdinar Untung Yuni Sukowati used his personal Instagram as a media to form political images, while signs in the form of icons, indexes and symbols both verbal and non-verbal were used in the digital campaign of Kusdinar Untung Yuni Sukowati in the Instagram account @mbakyuniselaludihatiaims to form an image of himself that is close to micro, small and medium businesses, cares for farmers, cares for the health of the Sragen community and likes innovation and is youthful.